Argumentação no discurso jurídico: técnicas argumentativas no habeas corpus. - Defassi, Ariane Dias Teixeira Leite (2016)
This dissertation focuses on pointing Rhetoric as theoretical and methodological reference in the production and analysis of legal discourse. For this particular purpose, the study of legal discourse is presented from the New Rhetoric angle, analyzing the power of persuasion through argumentation by means of the argumentative strategies of Perelman and Tyteca (2005): quasi-logical arguments, arguments based on an appeal to reality and arguments that stablish the structure of reality. The corpus encompasses two Habeas Corpus and respective judgments and enables the identification of the arguments used to persuade, as well as their intensity and possible results of whether the audience was convinced. The study points out the adequacy of the arguments listed in the Treaty of Argumentation to the legal discourse analysis. Finally, the reasonable use of the argumentative strategies proved itself to add consistency to the persuasive discourse, allowing the judge to reach well-founded decisions, being more equitable and just